2018
DOI: 10.1002/jbio.201800137
|View full text |Cite
|
Sign up to set email alerts
|

Stain‐free interferometric phase microscopy correlation with DNA fragmentation stain in human spermatozoa

Abstract: Acridine orange (AO) staining is used to diagnose DNA fragmentation status in sperm cells. Interferometric phase microscopy (IPM) is an optical imaging method based on digital holographic microscopy that provides quantitative morphological and refractive index imaging of cells in vitro without the need for staining. We have imaged sperm cells using stain-free IPM in order to estimate different cellular parameters, such as acrosome dry mass and size, in addition to an embryologist evaluation according to the Wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…This finding is consistent with an earlier study which showed the effect of head shape on fertilization rate . However, there is no clear conclusion that sperm head shape is significantly correlated with DNA integrity yet . In addition, our work revealed the significance and weight of other morphological parameters, such as acrosome size and acrosomal vacuole size, in predicting DNA integrity.…”
Section: Resultssupporting
confidence: 89%
“…This finding is consistent with an earlier study which showed the effect of head shape on fertilization rate . However, there is no clear conclusion that sperm head shape is significantly correlated with DNA integrity yet . In addition, our work revealed the significance and weight of other morphological parameters, such as acrosome size and acrosomal vacuole size, in predicting DNA integrity.…”
Section: Resultssupporting
confidence: 89%
“…We used a deep neural network to grade each live sperm cell according to its DNA fragmentation level. In contrast to Barnea et al [31] that shows only statistical difference for specific parameters in large populations of sperm cells measured by interferometry, with population overlaps, here we provide an individual-cell DNA measurement without staining.…”
Section: Dna Fragmentation Evaluation and Virtual Stainingmentioning
confidence: 90%
“…Next, the solution was placed on the cover slip and stained with acridine orange (0.19 mg ml -1 ) for several hours before imaging. [31] State of the Art Fertility Examination: For each donor, 10 µL of the sample were used for stainbased morphological evaluation, 10 µL for concentration and motility evaluation, 10 µL for stain-based DNA fragmentation evaluation, and the rest was used for stain-free interferometric assays. All state-of-the-art examinations were carried out according to the WHO2010 guidelines.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many different variations of phase microscopes have been created 6 . In parallel, inferometric phase microscopy (IPM) with optical imaging based on digital holographic microscopy has been introduced as a mean to investigate human spermatozoa 12 , 15 . The first attempt to simultaneously assess human spermatozoa using morphology, motility and quantitative stain-free inferometric imaging analysed with a deep-learning algorithm has already been presented 16 .…”
Section: Introductionmentioning
confidence: 99%